PERBANDINGAN HASIL PENGGUNAAN BEAUTY BLENDER, BRUSH, DAN KOMBINASI KEDUANYA DALAM APLIKASI FOUNDATION UNTUK KULIT BERJERAWAT PADA RIAS PENGANTIN INTERNASIONAL - Hasan, Hazizah Martina Sari; Megasari, Dindy Sinta; Lutfiati, Dewi; Wilujeng, Biyan Yesi (Jurnal Tata Rias, 2025)
Bridal makeup plays an important role in supporting the appearance of the bride, especially for brides who have acne-prone skin. The selection of the right foundation and application tools greatly affects the final result of the makeup. This study aims to analyze the differences in the results of foundation application using a beauty blender, brush, and a combination of both on acne-prone skin in International bridal makeup. This study uses an experimental method with a quantitative approach. The subjects consisted of three models with similar acne-prone skin characteristics, and involved 30 panelists. Data were collected through observation using research instruments and analyzed descriptively and through a one-way ANOVA test. The results showed a significance value of 0.00 (p <0.05), which indicated a significant difference between the three foundation application methods. The average assessment score showed that the application using a beauty blender scored 22.1 (fairly good category), a brush scored 23.3 (good category), and a combination of both scored the highest, namely 24.4 (very good category). Thus, it can be concluded that the use of a combination of a brush and a beauty blender provides the most optimal results in applying foundation to acne-prone skin in International bridal makeup. Keywords: Beauty Blender, Brush, Acne, Foundation, International Bride.